Community-acquired methicillin-resistant Staphylococcus aureus infection - García Apac, Coralith (2011)
Community-acquired methicillin-resistant Staphylococcus aureus infection is emerging worldwide. Skin and soft tissue infections are the common clinical presentations (eg, cellulitis, and abscess). Most infections are superficial but severe cases may develop causing severe sepsis, necrotizing fasciitis, pneumonia and death.